An evaluation method for the polishing and abrasion resistance of aggregate. Issue 5 (3rd July 2020) - Qian, Zhenyu; Hou, Yun; Dong, Yuanshuai; Cai, Yanxia; Meng, Lingjian; Wang, Linbing
Abstract : The polishing resistance performance and abrasion resistance performance of aggregate affect the long-term skid resistance and durability of the pavement, but there is still a lack of a comprehensive evaluation method to evaluate the aggregate performance in all aspects. This paper presents a study to develop a comprehensive evaluation method based on the assessments of four types of common aggregates in pavement engineering. The Wehner/Schulze polishing test and Micro-Deval abrasion test are used to respectively analyse the polishing resistance performance and abrasion resistance performance of the four aggregates. A comprehensive method for evaluating aggregate properties is proposed based on a laboratory test, the slope of the linear fitting line of the test results and the distribution of the results in the coordinate plot can reflect the performance of different aggregates, thus the coordinate plot is separated into four quadrants, aggregates falling into different quadrants are evaluated as good, fair and poor, respectively, so that to provide reference for aggregate screening or aggregate blending in pavement engineering.